Combined treatment of sorafenib and doxorubicin-loaded microbubble-albumin nanoparticle complex for hepatocellular carcinoma: A feasibility study - Lee, Seunghyun (PLoS One, 2020)
PURPOSE: To assess the feasibility of the combined sorafenib (SOR) and doxorubicin-loaded microbubble-albumin nanoparticle complex (DOX-MAC) treatment effect in an orthotopic rat model of hepatocellular carcinoma (HCC). MATERIALS AND METHODS: Sixty-two rats with N1-S1 hepatoma were divided into four groups according to the treatment methods, i.e. G1 (SOR and DOX-MAC; n = 12), G2 (SOR; n = 15), G3 (DOX-MAC; n = 12), G4 (DOX; n = 11), and G5 (normal saline; n = 12). We performed the theragnostic, contrast-enhanced ultrasound examination and treatment at the baseline, one-week, and two-weeks. Tumor volume and perfusion parameters were compared at each time point and the differences between all of the groups over time were analyzed using repeated measures ANOVA. We also analyzed the apoptotic index and microvessel density (MVD) per each tumor specimen in all of the groups. RESULTS: The tumors increased from the beginning in all of the groups to the final follow-up, whereas the tumor growth in the G1 group and the G2 group was inhibited during the treatment period compared to the baseline tumor volume (P = 0.016 and P = 0.031). The G1 group resulted in tumor growth inhibition compared to the control group (P = 0.008). The G1 group showed that the peak enhancement and wash-in area under the curve were lower than that of the G4 group (P = 0.010 and 0.022). However, there was no difference in perfusion parameters in the other treated group compared to control group. The MVD of the G1 group tumor was lower than that of the G4 group (P = .016). CONCLUSION: Our results suggest that the combination therapy of SOR and DOX-MAC can cause inhibition of tumor growth after treatment and that this therapy can be adequately monitored using the theragnostic DOX-MAC agent.